(3TQM efgGL GdGUhds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3jQjO eYQaI OdGFd Gdabg ef MjK GdLedI ef ZjQ GNJUGU hHYO Pdc HhQbI bGd UGMH GdeJf (B: (3bdfG GdeLJgO EPG GXf GdMce hLH Ydjg GdaJhi s
(3BNQgG (B:s
(3dci KHJ LhGR GdJbdjO ai GdaQhY ahLH UQa GdPe Edi GdJbdjO ai GdCUhd hdjcf gPG BNQ GdcdGe ai GdTQM s
(3HgG CKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3YHGQI GdTGQM JHOC Hbhdg TF s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs